Marijuana-Derived Cannabinoids Trigger a CB2/PI3K Axis of Suppression of the Innate Response to Oral Pathogens - Gu, Zhen; Singh, Shilpa; Niyogi, Rajarshi G.; Lamont, Gwyneth J.; Wang, Huizhi; Lamont, Richard J.; Scott, David A. (Frontiers in Immunology, 2019)
Cannabis use is an emergent risk factor for periodontitis, a chronic bacterial-induced disease of the supporting structures of the teeth. However, the mechanisms by which marijuana exposure predisposes to periodontal tissue destruction have yet to be elucidated. Therefore, we examined the influence of physiologically relevant doses of major marijuana-derived phytocannabinoid subtypes (cannabidiol [CBD]; cannabinol [CBN]; and tetrahydrocannabinol [THC], 1.0 μg/ml) on the interactions of three ultrastructurally variant oral pathogens, Porphyromonas gingivalis, Filifactor alocis and Treponema denticola with the immune system. CBD, CBN and THC each suppressed P. gingivalis-induced IL-12 p40, IL-6, IL-8 and TNF release while enhancing the anti-inflammatory cytokine, IL-10 from human innate cells. Similar phenomena were observed in F. alocis- and T. denticola-exposed human monocytes and human gingival keratinocytes. Higher phytocannabinoid doses (5.0 μg/ml) compromised innate cell viability and inhibited the growth of P. gingivalis and F. alocis, relative to unexposed bacteria. T. denticola, however, was resistant to all cannabinoid doses tested (up to 10.0 μg/ml). Pharmaceutical inhibition and efficient gene silencing indicated that a common CB2/PI3K axis of immune suppression is triggered by phytocannabinoids in vitro. This pathway does not appear to perpetuate through the canonical GSK3-dependent cholinergic anti-inflammatory pathway, the predominant endogenous inflammatory control system. In a repetitive, transient oral infection model, CBD also suppressed P. gingivalis-induced innate immune markers in wild-type mice, but not in CB2-/- mice. If such phenomena occur in humans in situ, environmental cannabinoids may enhance periodontitis via direct toxic effects on specific oral bacteria; by compromising innate cell vitality; and/or through a suppressed innate response to periodontal pathogens involving a CB2/PI3K signaling lineage.